An uncommon localization of black heels in a free climbing instructor. Issue 2 (17th December 2017) - Tammaro, Antonella; Magri, Francesca; Moliterni, Elisa; Parisella, Francesca Romana; Mondello, Matteo; Persechino, Severino
Abstract : Black heels, also known as talon noir or calcaneal petechiae, are asymptomatic superficial cutaneous haemorrhages of the feet, mostly seen as post‐traumatic lesions in young athletic individuals who practice sports such as tennis, football, or gymnastics. Here, we present a case of black heels in a young male rock climber.